Effects of Plyometric Jump Training on Electromyographic Activity and Its Relationship to Strength and Jump Performance in Healthy Trained and Untrained Populations: A Systematic Review of Randomized Controlled Trials. Issue 7 (July 2021) - Ramirez-Campillo, Rodrigo; Garcia-Pinillos, Felipe; Chaabene, Helmi; Moran, Jason; Behm, David G.; Granacher, Urs
Abstract : Abstract: Ramirez-Campillo, R, Garcia-Pinillos, F, Chaabene, H, Moran, J, Behm, DG, and Granacher, U. Effects of plyometric jump training on electromyographic activity and its relationship to strength and jump performance in healthy trained and untrained populations: a systematic review of randomized controlled trials. J Strength Cond Res 35(7): 2053–2065, 2021—This systematic review analyzed the effects of plyometric jump training (PJT) on muscle activation assessed with surface electromyography during the performance of strength and jumping tasks in healthy populations across the lifespan. A systematic literature search was conducted in the electronic databases PubMed/MEDLINE, Web of Science, and SCOPUS. Only randomized controlled studies were eligible to be included in this study. Our search identified 17 studies comprising 23 experimental groups and 266 subjects aged 13–73 years, which were eligible for inclusion. The included studies achieved a median Physiotherapy Evidence Database score of 6. No injuries were reported among the included studies. Significant PJT-related improvements were reported in 7 of 10 studies and in 6 of 10 studies for measures of muscle activation during the performance of strength and jumping tasks, respectively. Moreover, a secondary correlational analysis showed significant positive relationships ( r = 0.86; p = 0.012; r 2 = 0.74) between changes in muscle activation and changes in jump performance. However, from the total number ( n = 287) of muscle activation response variables analyzed for strength and jumping tasks, ∼80% ( n = 226) were reported as nonsignificant when compared with a control condition. In conclusion, PJT may improve muscle activation during the performance of strength and jumping tasks. However, conflicting results were observed probably arising from (a) studies that incorporated a large number of outcomes with reduced sensitivity to PJT, (b) methodological limitations associated to muscle activation measurement during strength and jumping tasks, and (c) limitations associated with PJT prescription. Future studies in this field should strive to solve these methodological shortcomings. Abstract : Supplemental Digital Content is Available in the Text.